2020
DOI: 10.1186/s42077-020-00081-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided thoracic paravertebral block vs pectoral nerve block for postoperative analgesia after modified radical mastectomy

Abstract: Background Thoracic paravertebral block may be used for analgesia after breast surgery. Ultrasound can be used during the whole technique of paravertebral block to increase success rate and decrease its complications. As well, pectoral nerve block is now used for pain relief after modified radical mastectomy with or without axillary clearance. Objective To compare thoracic paravertebral block and pectoral nerve block for postoperative analgesia after modified radical mastectomy Methods The study was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…After review, a further 1116 studies were excluded as not meeting our predefined criteria. Finally, 62 studies evaluating nine different regional analgesia techniques were used for the quantitative analysis 14–75 . The regional and local analgesia techniques were: erector spinae plane (ESP) block, local anaesthetic infiltration, paravertebral block (PVB), pectoserratus plane (PS) block, superficial serratus anterior plane (sSAP) block, retrolaminar block, deep serratus anterior plane (dSAP) block, rhomboid plane block, interpectoral-pectoserratus (IP-PS) block.…”
Section: Resultsmentioning
confidence: 99%
“…After review, a further 1116 studies were excluded as not meeting our predefined criteria. Finally, 62 studies evaluating nine different regional analgesia techniques were used for the quantitative analysis 14–75 . The regional and local analgesia techniques were: erector spinae plane (ESP) block, local anaesthetic infiltration, paravertebral block (PVB), pectoserratus plane (PS) block, superficial serratus anterior plane (sSAP) block, retrolaminar block, deep serratus anterior plane (dSAP) block, rhomboid plane block, interpectoral-pectoserratus (IP-PS) block.…”
Section: Resultsmentioning
confidence: 99%
“…It can also affect areas of the long thoracic and thoracodorsal nerves from potential compartment spaces 24 . Therefore, there are studies showing the efficacy of PECS I block in reducing postoperative pain in surgeries such as MRM 25,26 . Wahba et al 13 compared the analgesic effect and additional analgesic consumption of PECS I and TPV in women undergoing MRM.…”
Section: Discussionmentioning
confidence: 99%
“…24 Therefore, there are studies showing the efficacy of PECS I block in reducing postoperative pain in surgeries such as MRM. 25,26 Wahba et al 13 compared the analgesic effect and additional analgesic consumption of PECS I and TPV in women undergoing MRM. They observed that patients treated with PECS block within the first 24 h after surgery consumed significantly less morphine than those in the TPV group, and reported a longer time to first morphine request in the PECS group.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 16 ] However, most of the studies have been done on patients undergoing mastectomy or breast conservation surgeries. [ 17 18 19 20 ] To our knowledge, this study is the first to assess the efficacy of PEC blocks in fibroadenoma surgeries.…”
Section: Discussionmentioning
confidence: 99%